An Evaluation of the Chemical and Antibacterial Properties of the Mizo Traditional Medicine, Erythrina stricta - Lalawmpuii, Lucy; Tlau, Lalbiakngheti; Lalthanpuii, Pawi Bawitlung; Lalchhandama, Kholhring (Asian Journal of Biological and Life Sciences, 2026)
Background: Erythrina stricta Roxb. is a member of the legume’s family, Fabaceae, well-known among the Indian traditional healers for its numerous medicinal uses in various ailments. Different parts of the plant, such as its root, bark, leaves and flowers had been commonly used by many tribes across India. In the Mizo traditional medicine, the decoction of the bark is a remedy for various skin diseases, infection, stomach-ache and ulcers. This study was planned to authenticate the therapeutic applications upheld by the Mizo people. Materials and Methods: The chloroform extract of E. stricta bark was analysed for its secondary metabolite composition, antioxidant property and antibacterial activity against Gram-positive and Gram-negative species. Results: The main secondary metabolites in the plant extracts were identified as alkaloids, flavonoids and phenolic compounds. The antioxidant contents were determined as 28.86±0.95 mg/g quercetin equivalent for total flavonoid content, 9.11±0.15 mg/g gallic acid equivalent for total phenolic content, and 41.641±1.37 mg/g ascorbic acid equivalent for total antioxidant. The antioxidation capacity estimated using 2,2-Diphenyl-1-1-Picryldrazyl (DPPH) assays showed a half-maximal Inhibitory Concentration (IC50) value of 13.74±3.9, comparable to that of the standard butylated hydroxytoluene at IC50 of 10.53±2.7. The plant extract displayed a wide-range of antibacterial potential, effectively inhibiting the growth of Gram-negative bacteria including Klebsiella pneumoniae and Salmonella typhimurium, as well as Gram-positive species such as Bacillus cereus and Staphylococcus aureus, but not the Gram-negative Escherichia coli. Interestingly, the plant extract was also effective against antibiotic-resistant strains. The minimum inhibitory concentrations were determined as 2.5 mg/mL against S. aureus and S. typhimurium, and 5 mg/mL against B. cereus and K. pneumoniae. Conclusion: The findings substantiate E. stricta as a medicinally valuable plant having health beneficial properties. Its effectiveness against multidrug-resistance bacteria suggests that it could be a valuable source of broad-spectrum antibacterial compound. This is the first report of E. stricta as an effective agent against multidrug-resistant bacteria, thereby, indicating its importance in health and pharmaceutical development.
Keywords: Antibacterial; Antioxidant; Erythrina stricta; Medicinal Plant; Secondary Metabolites